2013
DOI: 10.1084/jem.20112615
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of NOTCH signaling ameliorates immune-mediated bone marrow failure of aplastic anemia

Abstract: Notch1 signaling sustains the proinflammatory behavior of Th1 cells, implicated in the development of aplastic anemia in humans and mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 61 publications
2
81
0
Order By: Relevance
“…High expression levels of Notch1/Hes1 presented in our study were similar to those reported in other autoimmune diseases [34][35][36][37].…”
Section: Discussionsupporting
confidence: 91%
“…High expression levels of Notch1/Hes1 presented in our study were similar to those reported in other autoimmune diseases [34][35][36][37].…”
Section: Discussionsupporting
confidence: 91%
“…One mechanism by which Notch signaling could have impacted SLEC differentiation is via its ability to regulate T-bet expression. Indeed, Tbx21 has been reported to be a direct transcriptional target of Notch in CD4 + T cells (14,15). In CD8 + T cells, inhibition of Notch signaling following in vitro stimulation of CD8 + T cells leads to reduced expression of T-bet, but, unfortunately, the direct binding of the NICD to the Tbx21 gene was not evaluated in this study (23).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, there is evidence that Tbx21 is a Notch target gene (14,15,23). Therefore, we evaluated whether the reduced generation of SLECs in the absence of Notch1/2 correlated with a decrease in T-bet expression.…”
Section: Defective Slec Generation Is Not the Consequence Of Reduced mentioning
confidence: 99%
See 1 more Smart Citation
“…However, interpretation was difficult given possible non-cellautonomous effects of overexpressed Notch ligands, the lack of direct genetic demonstration, and the artificial nature of the gain-of-function experimental systems. More recently, several laboratories used in vivo loss-of-function strategies to evaluate the role of Notch signaling in alloimmunity (41,(117)(118)(119)(120)(121)(122)(123)139). These studies reached concordant conclusions that Notch functions as a major proinflammatory signaling pathway promoting pathogenic alloreactivity, in both GVHD and transplant rejection.…”
Section: Early Insights On Notch Signaling In Alloimmunitymentioning
confidence: 99%